Observations of large‐amplitude, parallel, electrostatic waves associated with the Kelvin‐Helmholtz instability by the magnetospheric multiscale mission. Issue 17 (3rd September 2016) - Wilder, F. D.; Ergun, R. E.; Schwartz, S. J.; Newman, D. L.; Eriksson, S.; Stawarz, J. E.; Goldman, M. V.; Goodrich, K. A.; Gershman, D. J.; Malaspina, D. M.; Holmes, J. C.; Sturner, A. P.; et al.
Abstract: On 8 September 2015, the four Magnetospheric Multiscale spacecraft encountered a Kelvin‐Helmholtz unstable magnetopause near the dusk flank. The spacecraft observed periodic compressed current sheets, between which the plasma was turbulent. We present observations of large‐amplitude (up to 100 mV/m) oscillations in the electric field. Because these oscillations are purely parallel to the background magnetic field, electrostatic, and below the ion plasma frequency, they are likely to be ion acoustic‐like waves. These waves are observed in a turbulent plasma where multiple particle populations are intermittently mixed, including cold electrons with energies less than 10 eV. Stability analysis suggests a cold electron component is necessary for wave growth. Key Points: Large‐amplitude electrostatic waves are observed in the middle of a Kelvin‐Helmholtz vortex Waves follow fresh mixing of plasma populations with cold electrons present Cold electrons may be needed to promote wave growth